CHARACTERIZATION OF XANTHOMONAS ORYZAE PV. ORYZAE FROM MAJOR RICE GROWING REGIONS OF KARNATAKA - SHIVALINGAIAH; S. UMESHA (The Bioscan, 2011)
Among many bacterial diseases bacterial leaf blight of rice caused by Xanthomonas oryzae pv. oryzae is a major biotic constraint and is wide spread in Asia, including India. In the present study field survey was undertaken in the major rice growing regions of Karnataka, a southern state of India which revealed the presence of bacterial leaf blight incidence ranging from 12 to 75%. The pathogen was isolated from the seeds and infected plant materials collected during field survey. Xanthomonas oryzae pv. oryzae was detected from rice seeds and also from plant material and its identity was confirmed by morphological, physiological and biochemical tests, hypersensitive and pathogenicity tests. The scenario and severity of bacterial leaf blight in Karnataka is discussed in the present study.